PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP RETURN ON ASSETS PADA PT AKASHA WIRA INTERNASIONAL TBK PERIODE 2013-2023 - Munadya Mulkiyah Hasanah; Ria Rosalia Simangunsong (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the effect of Cash Turnover and Accounts Receivable Turnover on Return on Assets, both partially and simultaneously, at PT Akasha Wira International Tbk during the 2013–2023 period. The research method used is a quantitative method. The population in this study consists of all financial reports of PT Akasha Wira International Tbk. The sample used includes the statements of financial position and income statements from 2013 to 2023, obtained from the company's official website. The data analysis techniques employed are Descriptive Analysis, Classical Assumption Tests, Coefficient of Determination Test, Multiple Linear Regression Analysis, and Hypothesis Testing. The research results showed that the Adjusted R Square value was recorded at 0.841 or 84.1%. This indicates that all independent variables together were able to explain 84.1% of the variation in the dependent variable (ROA). Meanwhile, the remaining 15.9% was influenced by other factors not included in this test analysis. Furthermore, the research results from the t-test show that the t-value for Cash Turnover is -5.099, which is greater than the t-table value of 2.306 (-5.099 > 2.306), with a significance value of 0.001, which is less than 0.05 (0.001 < 0.05). Therefore, it can be concluded that Cash Turnover has a significant negative effect on Return on Assets. Meanwhile, the t-value for Accounts Receivable Turnover is 3.460, which is greater than the t-table value of 2.306 (3.460 > 2.306), with a significance value of 0.009, which is less than 0.05 (0.009 < 0.05). Thus, it can be concluded that Accounts Receivable Turnover has a significant positive effect on Return on Assets. Furthermore, Cash Turnover and Accounts Receivable Turnover simultaneously have a significant positive effect on Return on Assets (ROA) at PT Akasha Wira International Tbk for the 2013–2023 period, as indicated by an F-value of 27.355, which is greater than the F-table value of 4.46 (27.355 > 4.46), and a significance value of 0.000, which is less than 0.05